2022
DOI: 10.3389/fpubh.2022.1012509
|View full text |Cite
|
Sign up to set email alerts
|

Targeting food parenting practices to prevent early child obesity risk requires a different approach in families with a lower socioeconomic position

Abstract: September CITATIONLarsen JK, Karssen LT and van der Veek SMC ( ) Targeting food parenting practices to prevent early child obesity risk requires a di erent approach in families with a lower socioeconomic position. Front. Public Health : . doi: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The intervention reflected this through quotes and short audio stories from the interview transcripts to support and contextualise the messaging provided. Using social context in interventions targeting feeding practices among families with a lower socioeconomic position was a key recommendation from Larsen et al 60 This research has demonstrated that creative and innovative approaches can meet the needs of parents with complex needs.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention reflected this through quotes and short audio stories from the interview transcripts to support and contextualise the messaging provided. Using social context in interventions targeting feeding practices among families with a lower socioeconomic position was a key recommendation from Larsen et al 60 This research has demonstrated that creative and innovative approaches can meet the needs of parents with complex needs.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity is even more alarming, in vulnerable subpopulations (e.g., families with a low-SES) where unhealthy dietary patterns, higher levels of physical inactivity and sedentary behaviour have been reported and consequently there is a higher overweight/ obesity prevalence compared to the general population. [7][8][9][10][11][12] Except from the living environment, home environment and family feeding behaviours play important role in child's eating behaviours and weight status, especially during first years of life. Family is the first and most important social context where children adopt and gradually develop eating behaviours 13 and subsequently they shape their food choices, lifestyle quality and weight status.…”
Section: Introductionmentioning
confidence: 99%
“…25 More specifically, studies among families with higher SES outnumber those among families with lower SES and most high-quality studies among parents with lower SES have investigated feeding styles instead of general parental practices, so direct comparisons are difficult to make. 9,10 To our knowledge, this study is the first to assess the association between parental practices and children's lifestyle indices with childhood overweight/obesity risk in a large sample of children 4-12 years old from the Feel4Diabetes study conducted in families from low-SES regions in Europe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations